For the hell of it : the life and times of Abbie Hoffman - Raskin, Jonah, 1942- (University of California Press, 1996)
Drawing on his own twenty-year relationship with Hoffman, hundreds of interviews with friends, family members, and former comrades, and careful scrutiny of FBI files, court records, and public documents, Raskin provides the best account we have of this mercurial figure. He takes us from Hoffman's childhood in Worcester, Massachusetts, through his civil rights and antiwar activities - in particular his roles in the 1968 Democratic National Convention and the notorious Chicago Conspiracy trial the next year. Raskin chronicles Hoffman's cocaine bust, his years underground during the seventies, and his alternating fits of manic hyperactivity and paralyzing depression. When he took his own life in 1989, Hoffman was both larger than life and a deeply troubled soul.